Cardiovascular, metabolic, and hormonal parameters in professional tennis players - Konig, D.; Huonker, M.; Schmid, A.; Halle, M.; Berg, A.; Keul, J. (Medicine & Science in Sports & Exercise, 2001)
During the past decade, the physical and mental stress in professional tennis has been constantly increasing. The overall intensity in tennis ranges between 60 and 70% of maximum oxygen uptake and the energy requirements are mainly provided by aerobic energy metabolism. Therefore, particularly with respect to the duration of the tournaments and the length of the matches, a good aerobic capacity promotes continuous success in professional tennis. During frequent periods of high intensity, however, muscular energy is derived from anaerobic glycolysis. Therefore, sports-specific conditioning programs in tennis should improve both glycolytic and oxidative muscular metabolism. Years of training and competition induce a number of cardiovascular and metabolic adaptations: an increase in heart size in terms of an athlete's heart, higher oxygen uptake capacity, improved muscular oxidative enzyme activities, reduced baseline catecholamine levels, and a lower resting heart rate. In addition, tennis induces side-specific increments in bone density, bone diameter, and bone length of the upper extremity. Furthermore, structural and functional adaptations of the conducting arteries in the preferred arm could be demonstrated in professional tennis players. In conclusion, tennis is a very complex sport involving strength, power, speed, agility and explosiveness, as well as endurance components. Scientific data on exercise-related cardiovascular and metabolic parameters in professional tennis are important to evaluate the players individual fitness level and will help to improve sports-specific conditioning programs. This in turn will not only enhance performance but also prevent overstrain and burnout syndromes.